Relationship between Cognitive and Sleep–wake Variables in Asymptomatic Offspring of Patients with Late-onset Alzheimer’s Disease - Abulafia, Carolina; Duarte-Abritta, Bárbara; Villarreal, Mirta F.; Ladrón-de-Guevara, María S.; García, Celeste; Sequeyra, Geraldine; Sevlever, Gustavo; Fiorentini, Leticia; Bär, Karl-Jürgen; Gustafson, Deborah R.; Vigo, Daniel E.; Guinjoan, Salvador M. (Frontiers in Aging Neuroscience, 2017)
Early neuropathological changes characteristic of late-onset Alzheimer´s disease (LOAD) involve brain stem and limbic structures that regulate neurovegetative functions, including sleep-wake rhythm. Indeed, sleep pattern is an emerging biomarker and a potential pathophysiological mechanism in LOAD. We hypothesized that cognitively asymptomatic, middle-aged offspring of patients with LOAD would display a series of circadian rhythm abnormalities prior to the onset of objective cognitive alterations. We tested 31 children of patients with LOAD (O-LOAD) and 19 healthy individuals without family history of AD (CS) with basic tests of cognitive function, as well as actigraphy measures of sleep-wake rhythm, cardiac autonomic function, and bodily temperature. Unexpectedly, O-LOAD displayed subtle but significant deficits in verbal episodic memory (RAVLT delayed recall 10.6 ± 0.4 vs. 8.6 ± 0.6, t=4.97, df=49, p<0.01) and language (Weschler´s vocabulary 51.4 ± 1.3 vs. 44.3 ± 1.5, t=2.49, df=49, p<0.001) compared to CS, even though all participants had results within the clinically normal range. O-LOAD showed a phase-delayed rhythm of body temperature (2.56 ± 0.47 h vs 3.8 ± 0.26 h, t=2.48, df=40, p=0.031). Cognitive performance in O-LOAD was associated with a series of cardiac autonomic sleep-wake variables; specifically indicators of greater sympathetic activity at night were related to poorer cognition. The present results suggest sleep pattern deserves further study as a potential neurobiological signature in LOAD, even in middle-aged, at risk individuals.